EUGLYCEMIC DIABETIC KETOACIDOSIS (DKA) - A STUDY OF TWO CASES - WA, Siti Sanaa; AR, Anilah; HR, Ijaz (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Euglycemic DKA is characterised by increased anion gap metabolic acidosis, ketonemia or ketonuria and normal blood glucose levels. Here we describe 2 different cases of euglycemic DKA. CASE 1 A 40-year-old lady who was newly diagnosed with type 2 diabetes mellitus was started on Empaglifozin 12.5 mg OD by her general practitioner. Four days later, she presented with acute abdominal pain and gastrointestinal losses. Further history revealed total carbohydrate restriction one week prior to presentation in an effort to improve her glucose control. Upon admission there was severe metabolic acidosis (pH 7.035 and HCO3 6.3 mEq/L on arterial blood gas analysis), slightly elevated capillary blood glucose (CBG) (8.0 mmol/L), and high serum ketones (4.2 mEq/L). Fluid resuscitation with normal saline was initiated, and dextrose and insulin infusion were maintained. We withheld the sodium glucose cotransporter 2 inhibitor (SGLT2i) and she was discharged well with low dose basal bolus insulin. CASE 2 A 44-year-old lady with background history of diabetes mellitus, hypertension, hyperlipidemia and morbid obesity, was electively admitted for laparoscopic Rouxen-Y gastric bypass surgery. She was prescribed with a very low-calorie diet as per protocol 2 weeks prior to surgery. Postoperatively she developed vomiting accompanied by metabolic acidosis with persistent ketosis, requiring ICU admission. She was put on continuous insulin and dextrose infusion and subsequently referred to our dietitian, aiming for total calorie intake of 800 kcal/day. Glucose was well controlled in the ward with eventual resolution of acidosis and ketosis. She was discharged well. RESULTS We illustrated 2 cases of euglycemic DKA: one was precipitated by SGLT2i use and the other by prolonged starvation with severe carbohydrate restriction prior to bariatric surgery. CONCLUSION High clinical suspicion is required to diagnose euglycemic DKA, as normal blood glucose levels masquerade the underlying DKA and may cause a delay in diagnosis and institution of appropriate therapy.